Hot showcase design with utilization of waste heat from Cold Showcase’s Condenser - Christopher Pratama Djaya (Petra Christian University, 2017)
The need of warm showcase is on the rise, but warm showcase uses a lot of energy. Most user of warm showcase also have cold showcase. One component of cold showcase produces high enough heat and did not utilized. Therfore in this thesis, condenser designed to be utilizes for warm showcase (waste recovery). In this study, the condenser is designed to meet the heat energy need of warm showcase without using heater. This system is using automation.The design of condenser has a length of pipe of 5,3 m with a capacity of 0,4m3 reach temperature 45oC at 20 minutes. In the utilization of the condenser as a heater on warm showcase, the performance of cool showcase is not disturbed.